The bookshop of the world : making and trading books in the Dutch Golden Age - Pettegree, Andrew; Weduwen, Arthur der (Yale University Press, 2019)
The Dutch Golden Age has long been seen as the age of Rembrandt and Vermeer, whose paintings captured the public imagination and came to represent the marvel that was the Dutch Republic. Yet there is another, largely overlooked marvel in the Dutch world of the seventeenth century: books. In this fascinating account, Andrew Pettegree and Arthur der Weduwen show how the Dutch produced many more books than pictures and bought and owned more books per capita than any other part of Europe. Key innovations in marketing, book auctions, and newspaper advertising brought stability to a market where elsewhere publishers faced bankruptcy, and created a population uniquely well-informed and politically engaged. This book tells for the first time the remarkable story of the Dutch conquest of the European book world and shows the true extent to which these pious, prosperous, quarrelsome, and generous people were shaped by what they read.